Rampa Campur (Mixed Ingredients) in Nomenclature of Minahasan Culinary Ingredients as Food Security - Pamantung, Rina P.; . Porong, Viekson J; Wowor, Meity; Monoarfa, Stanly; M. Lontoh, Irma (Indonesian Journal of Multidisciplinary Science, 2025)
Food security is a priority program of President of R I. The government has allocated Rp118 trillion for food security programs in 2025, focusing on various initiatives to enhance food availability and access. Food security close related to the traditional food include Minahasan culinary and its ingredients (spicy). So the study focuses on the Rampa campur in Nomenclature of Minahasan ingredients. In the Minahasan community, the traditional food’s spices (ingredients) are uniquely differentiated based on the use of local languages in certain Minahasan regions. The problem is what are the lingual forms of the Rampa campur in Nomenclature of Minahasan ingredients as food security and its meaning. This research uses a descriptive qualitative method through a linguistics synchronic and gastronomic linguistic approach. The theory of syntax (Givon, 1984) and morphology are applied. The lingual forms of the Rampa campur in Nomenclature of Minahasan ingredients are words and phrases as results of research. Kekuru ‘kemangi’ ( Ocimum citriodonum)., and salimbata ‘serai’ (Cymbopogon Citratus) are words. Kekuru as raw material in woku and tinutuan. Sere is used in pangi, tinoransak, kotei, saut, and ayam woku isi di bulu . Furthermore, phrases consist of Lemong Cui ‘jeruk nipis’, is call lemong ikang (Citrus microcarpa), and Daong lemong ‘daun jeruk’ ( Lat citruss aurantifolia). Lemong cui is a basic ingredients in ikang bakar rica. While, Daun lemong is used in pangi, tinoransak, kotei, saut, dan ayam woku isi di bulu. The patterns are 1). Noun +noun; 2) and Noun + Adjective.